CHALLENGES TO THE FUNCTIONING OF THE UKRAINIAN ECONOMY IN THE CONDITIONS OF WAR AND PANDEMIC COVID-19 (Development Service Industry Management, 2023)
The article analyzes the functioning of the Ukrainian economy during the full-scale invasion of Russia and the COVID-19 pandemic. It was established that since 2014, Ukraine's economy functioned in the conditions of a hybrid war between the aggressor country and Ukraine and demonstrated relative stability, quickly moving from the phase of crisis to the phase of recovery growth. It found that from 2021 to early 2022, the economy was suffering from the effects of the ongoing COVID-19 pandemic and was further weakened by the pandemic, having not fully recovered from the shock of the hybrid war unleashed by the aggressor country in 2014. As a result of the full-scale war that began, the economy of Ukraine underwent changes. It was determined that the Government supports programs and measures to stabilize the economy of Ukraine in the conditions of martial law, in particular, it implemented: the program of relocation of enterprises to safe territory; formation of a state order for products; implementation of a number of important decisions on deregulation; new tax policy aimed at reducing the fiscal burden on enterprises; interest-free lending programs for all areas of business. It has been established that in 2022 the fall in GDP amounted to more than 35%. It was determined that one of the current trends is the continuation of the decline in investment activity during the war, which was partially compensated by the forced investment of business and the state in the acquisition and installation of a significant number of alternative sources of electricity. It is established that slight growth in real GDP is expected in 2023 by 0.3%. It was found that the support of economic growth and financial stability should be a priority of monetary policy. It was determined that until the creation of a qualitatively new and stable system of economic security in Ukraine, high risks will remain for a long time due to the uncertainty of the development of events. This, in turn, restrains the free flow of capital into the Ukrainian economy.
Keywords: war economy; economic development; stability; financial support; martial law; COVID-19